A Two‐Coordinate Cyclic (Alkyl)(amino)silylene: Balancing Thermal Stability and Reactivity. Issue 50 (15th November 2016) - Kosai, Tomoyuki; Ishida, Shintaro; Iwamoto, Takeaki
Abstract: A crystalline two‐coordinate cyclic (alkyl)(amino)silylene (1 ) was successfully synthesized and isolated. Its 29 Si NMR and UV/Vis spectra indicate that the electronic properties of1 fall between those of cyclic dialkylsilylenes and diaminosilylenes. At very low temperature, the color of a solution of1 turned from colorless to yellow, which was monitored by UV/Vis spectroscopy. DFT calculations supported the hypothesis that head‐to‐head dimers (disilenes) with a very long Si–Si distance are formed at such low temperatures. Although1 is thermally stable, it readily undergoes cycloadditions, Si−H insertions, and photochemical reactions with benzene similar to dialkylsilylenes. At higher temperatures, 1 is also susceptible to intermolecular benzylic C−H insertion reactions, as well as unprecedented dehydrogenation reactions with cyclohexa‐1, 4‐diene and 9, 10‐dihydroanthracene to afford benzene and anthracene, respectively. Abstract : It takes two : A two‐coordinate cyclic (alkyl)(amino)silylene was synthesized and isolated in the form of colorless crystals. Spectroscopic data indicate that the electronic properties of1 are intermediate to those of cyclic dialkylsilylenes and diaminosilylenes. Silylene1 is thermally stable, but undergoes a reversible dimerization at low temperature. Reactions between1 and cyclohexa‐1, 4‐diene or 9, 10‐dihydroanthracene afford benzene and anthracene, respectively.